A subcellular proteome atlas of the yeast Komagataella phaffii. Issue 1 (10th January 2020) - Valli, Minoska; Grillitsch, Karlheinz; Grünwald-Gruber, Clemens; Tatto, Nadine E; Hrobath, Bernhard; Klug, Lisa; Ivashov, Vasyl; Hauzmayer, Sandra; Koller, Martina; Tir, Nora; Leisch, Friedrich; Gasser, Brigitte; et al.
ABSTRACT: The compartmentalization of metabolic and regulatory pathways is a common pattern of living organisms. Eukaryotic cells are subdivided into several organelles enclosed by lipid membranes. Organelle proteomes define their functions. Yeasts, as simple eukaryotic single cell organisms, are valuable models for higher eukaryotes and frequently used for biotechnological applications. While the subcellular distribution of proteins is well studied in Saccharomyces cerevisiae, this is not the case for other yeasts like Komagataella phaffii (syn. Pichia pastoris ). Different to most well-studied yeasts, K. phaffii can grow on methanol, which provides specific features for production of heterologous proteins and as a model for peroxisome biology. We isolated microsomes, very early Golgi, early Golgi, plasma membrane, vacuole, cytosol, peroxisomes and mitochondria of K. phaffii from glucose- and methanol-grown cultures, quantified their proteomes by liquid chromatography-electrospray ionization-mass spectrometry of either unlabeled or tandem mass tag-labeled samples. Classification of the proteins by their relative enrichment, allowed the separation of enriched proteins from potential contaminants in all cellular compartments except the peroxisomes. We discuss differences to S. cerevisiae, outline organelle specific findings and the major metabolic pathways and provide an interactive map of the subcellular localization of proteins in K. phaffii . Abstract : About 2000 intracellular proteins of the methylotrophic yeast Komagataella phaffii were quantified and for most of them the organelle localization was attributed.